Tightly Controlled Expression of bHLH142 Is Essential for Timely Tapetal Programmed Cell Death and Pollen Development in Rice - Ko, Swee-Suak; Li, Min-Jeng; Lin, Yi-Jyun; Hsing, Hong-Xian; Yang, Ting-Ting; Chen, Tien-Kuan; Jhong, Chung-Min; Ku, Maurice Sun-Ben (Frontiers in Plant Science, 2017)
Male sterility is important for hybrid seed production. Pollen development is regulated by a complex network. We previously showed that knockout of bHLH142 in rice (Oryza sativa) causes pollen sterility by interrupting tapetal programmed cell death (PCD) and bHLH142 coordinates with TDR1 to modulate the expression of EAT1. In this study, we demonstrated that overexpression of bHLH142 (OE142) under the control of the ubiquitin promoter also leads to male sterility in rice by triggering the premature onset of PCD. Protein of bHLH142 was found to accumulate specifically in the OE142 anthers. Overexpression of bHLH142 induced early expression of several key regulatory transcription factors in pollen development. In particular, the upregulation of EAT1 at the early stage of pollen development promoted premature PCD in the OE142 anthers, while its downregulation at the late stage impaired pollen development by suppressing genes involved in pollen wall biosynthesis, ROS scavenging and PCD. Collectively, these events led to male sterility in OE142. Analyses of related mutants further revealed the hierarchy of the pollen development regulatory gene network. Thus, the findings of this study advance our understanding of the central role played by bHLH142 in the regulatory network leading to pollen development in rice and how overexpression of its expression affects pollen development. Exploitation of this novel functionality of bHLH142 may confer a big advantage to hybrid seed production.